Potensi Larva Black Soldier Fly Sebagai Pengurai Limbah Organik Melalui Budidaya Maggot untuk Pakan Unggas dan Ikan - Febrian; Razak, Abdul; Yuniarti, Elsa; Handayuni, Linda (Jurnal Ekologi, Masyarakat dan Sains, 2024)
Indonesia is the country with the fourth largest population in the world due to its high production of both inorganic and organic garbage. There is an effort made by society in reducing organic waste, which is to recycle organic wastes by bioconversion methods. Previous research has recycled organic garbage into a medium for the cultivation of maggot or known as Larva Black Soldier Fly, which can be used as feed for poultry or fish. This method is used to find, evaluate, and interpret research findings that relate to a particular subject or phenomenon. The result of this research is a new innovation in the reduction of organic garbage through the cultivation of maggot or known Black Soldier Fly Larva is still not maximum. There should be a participatory development effort among societies with a community or wider social sphere to encourage transformative action using the latest media.